INFLUENCE OF UTILIZED LOAD OF DRIVE OF COMPRESSING STATION UPON PARAMETERS OF GTP - A. A. Abrazovski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Today it is required to use secondary energy resources (STR), which we have in gas-transport system of the country, more efficiently. In this system (STR) smoke gases of gas transforming aggregates with turbogas drive installations are presented primarily.For using STR of turbogas drives it is necessary to forecast heat exchange equipment installation, this causes the growth of aerodynamic resistance of exhaust channel. This influences on all plant’s work. It was experimentally proved that the usage of utilized equipment influences upon increasing  of power efficiency. For this reason the perturbation method was used, which allow to determine rate of influence. Convenience of this method is that the solution can be obtained in the form of evident analytical dependence and it does not depend on formulated problem, number of variable and definite relations between them.Using the perturbation method influence efficiency was obtained, which influences on exhaust channel resistance changes and as a result changes power efficiency and in the whole plant’s efficiency. Besides, in this article the dependence of influence efficiency from stating parameters of cycle was presented in graphs: temperature of burning products before turbine and air compression.